Effects of compliance and non-compliance to recommended care instructions to compression sportswear quality - Lontoc, Eianna Grace L.; Rayala, Maria Monica E. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
Care label is an essential part of any garment for it provides instructions on how it can be well taken care of. The researcher‟s personal experience was the reason behind the interest in studying consumers‟ knowledge and compliance to care labels. This descriptive study aimed to know the effects on the quality of compression sportswear based on the laundering methods of the UP female varsity student respondents who do not comply with the recommended care instructions. The purpose of this study is to promote proper garment care in order to prolong the life cycle and usage of compression sportswear. Selected through systematic random sampling, thirty-one respondents participated in the study. Only eight of them do their own laundry and four out of the eight do not comply with the recommended care instructions for their compression sportswear. Three samples of compression sportswear were provided; one as control sample and the other two as test samples. Test sample 1 was for compliance to the recommended care instructions of the compression sportswear administered in the laboratory. The laundering methods of the respondents who do not comply with care instructions were applied to test sample 2 by the researcher. Both test samples were submitted to the same laboratory and were compared to the control sample for quality evaluation. The research concluded that various possible factors cause the respondents not to comply with the recommended care instructions. Based on the test reports, the test sample 2 washed using the laundering methods of the selected respondents have shown significant changes in dimension compared to test sample 1. These effects are detrimental to the quality of compression sportswear as they slowly and accumulatively reduce the life cycle of the garment. Thus, these effects also minimize its function as compression sportswear which must retain its elasticity to fully serve its purpose.
submitted June 2018
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman.
Keywords: Sport clothes -- Philippines; Clothing care labels -- Philippines